Effect of 3,4,4 '-trichlorocarbanilide on growth of lactic acid bacteria contaminants in alcoholic fermentation - Oliva-Neto, P. D.; Yokoya, F. (Elsevier B.V., 1998)
3,4,4'-trichlorocarbanilide (TCC) was rested as a new method of bacterial growth control for S. cerevisiae alcoholic fermentations of diluted high test molasses (HTM). Minimal inhibitory concentration (MIC) was tested to determine the necessary concentration of TCC to control bacterial growth. The fed-batch alcoholic fermentation process was used with cell recycle similar to industrial conditions and Lactobacillus fermentum CCT 1407 was mixed in the first inoculum to grow with the yeast. Yeast extract was added into the must to stimulate bacterial growth. The best results of TCC's MIC to bacterial growth of Lactobacillus fermentum and Leuconostoc mesenteroides (< 0.125-1.0 mu g/ml) and Saccharomyces cerevisiae (16 mu g/ml) occurred when it was combined with sodium dodecylsulphate (SDS) in a 1: 4 TCC/SDS ratio (wt/wt) in distilled water solution. 1.8 g/l TCC entrapped in calcium alginate added to the must with yeast extract inhibited the growth of Lactobacillus fermentum CCT 1407 maintaining a controlled acidity, higher yeast viability and up to 20.8% of improvement in the average of alcoholic efficiency. Addition of 0.075 g/l TCC entrapped in calcium alginate and 1.67 mg/l SDS in the wort with yeast extract (0-5.0 g/l), inhibited and controlled the extensive bacterial contamination for 19 cycles of fermentation. (C) 1998 Published by Elsevier B.V. Ltd.
Keywords: growth; control; Lactobacillus fermentum; 3,3,4 '-trichlorocarbanilide; alcoholic fermentation